ANALISIS PENGARUH CITRA MEREK, KEWAJARAN HARGA, DAN LINGKUNGAN FISIK TERHADAP KEPUASAN KONSUMEN PADA TOWER CAFE TEMBALANG - Wijaya, Fransiska Sari; Hidayati, Retno (Faculty of Economics and Business Diponegoro University, 2020)
This research came from the dissatisfaction problem that occured at Tower Cafe Tembalang. Dissatisfaction that happens can cause things that are detrimental to the sustainability of the cafe, such as the possibility of the emergence of negative WOM and low interest in repurchasing the product. One strategy that is generally used to overcome this problem is to increase customer satisfaction. Therefore, this research aims to understand what factors that can increase customer satisfaction. This research also wanted to find out whether there is an influence of brand image, price reasonableness, and physical environment toward customer satisfaction in Tower Cafe Tembalang.The population in this research was consumer of Tower Cafe Tembalang. Data obtained through questionnaires from 150 samples, using non-probability approach, purposive sampling. Then, the data is processed and analyzed using multiple linear regression and T test.The result showed that brand image, price reasonableness, and physical environment have a significant positive effect on customer satisfaction. In other words, all hypotheses that said there are a positive influence between brand image, price reasonableness, and physical environment on customer satisfaction, are accepted.